1997
DOI: 10.1086/513775
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Gynecologic Disease Among Hospitalized Women with Human Immunodeficiency Virus Infection

Abstract: We offered standardized gynecologic examinations to consecutive women admitted to an AIDS-designated inpatient medical service; 65 (97%) of 67 women consented to the examination. The median CD4+ T lymphocyte count was 54/mm3. Only 9% of the women were admitted for primary gynecologic or genitourinary diagnoses; however, on evaluation, 83% of these women had gynecologic disease. The overall prevalences of vaginitis, cervical dysplasia, genital condylomata, genital herpes, and pelvic inflammatory disease were 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
0
14
2
1
Order By: Relevance
“…11 In a study of 65 women admitted to an inpatient AIDS service, 83% had coexisting gynecological disease, although only 9% were admitted with a primary gynecological problem. 3 The prevalence of cervical dysplasia in HIV-infected women varies from 11% to 60%, [12][13][14] rates approximately 10-fold higher than that observed among HIV-uninfected women. 15 Studies have shown that Pap smear sensitivity and specificity are comparable in HIV-infected and uninfected women, 12 although mild cytological atypia, such as atypical cells of undetermined significance (ASCUS) and inflammation, are more likely to be associated with dysplasia in HIV-infected women than in HIV-uninfected women and should prompt follow-up, generally including colposcopic examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In a study of 65 women admitted to an inpatient AIDS service, 83% had coexisting gynecological disease, although only 9% were admitted with a primary gynecological problem. 3 The prevalence of cervical dysplasia in HIV-infected women varies from 11% to 60%, [12][13][14] rates approximately 10-fold higher than that observed among HIV-uninfected women. 15 Studies have shown that Pap smear sensitivity and specificity are comparable in HIV-infected and uninfected women, 12 although mild cytological atypia, such as atypical cells of undetermined significance (ASCUS) and inflammation, are more likely to be associated with dysplasia in HIV-infected women than in HIV-uninfected women and should prompt follow-up, generally including colposcopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…2 Women infected with HIV are at increased risk for many gynecological problems, including vaginitis, genital herpes, genital condylomata, pelvic inflammatory disease (PID), and lower genital tract dysplasia and neoplasia. [3][4][5] HIV-infected women have higher rates of cervical, vulvar, vaginal, and anal intraepithelial lesions than HIVuninfected women, 6 and invasive cervical cancer is an AIDSdefining illness. Based on our clinical experiences, however, we hypothesized that adherence to recommended gynecological care in our urban HIV clinic environment was poor.…”
Section: Introductionmentioning
confidence: 99%
“…HIVC women have a higher prevalence and incidence of comorbid HPV infection than HIV women (Ahdieh et al, 2001;Branca et al, 2003;Frankel, Selwyn, Mezger, & Andrews, 1997). HPV is one of the most common sexually transmitted infections in the United States.…”
mentioning
confidence: 99%
“…Among HIV-infected women, there is excessive morbidity due to STDs and gynecologic disorders [5][6][7][8][9]. The need to prevent and control manifestations applies worldwide, but it is in the nonindustrialized world that gynecologic infections in HIV infection have their greatest impact, not only influencing HIV transmission but adding the dimension of vertical transmission of HIV to newborns [10].…”
mentioning
confidence: 99%